Mass Production of Field Planting Stock of Dendrocalamus strictus through Macro-proliferation-a Technology - Kumar, Adarsh (Indian Forester, 1991)
The technology developed for production field planting stock of D. strictus on mass scale has been described. The advantage of this technology is that it is simple, easy, quick and involves the use of locally available materials. The planting stock deleloped with this technology, Planted in the field established well and have shown vigorous growth and culm formation in 6 months. A plan has been developed to produce 36,000 field plantable seedlings of D strictusd through macroproliferation every year for several years, without seed. Depending upon the facilities available, the target for the production of planting stock can be increased in the multiples of 36,000 each year. The dependance on bamboo seed is totally eliminated for mass production of field plantable bamboo planting stock from second year onwards. The planting stocks developed through macro-proliferation remain small in size which is additional advantage, as these are easy to handle and transport.